The Lobotomy Letters : The Making of American Psychosurgery - Raz, Mical (Book collections on Project MUSE., 2013)
The Lobotomy Letters gives an account of the widespread acceptance of this controversial procedure. Drawing from original correspondence penned by lobotomy patients and their families as well as from the professional papers of lobotomy pioneer and neurologist Walter Freeman, the volume reconstructs how physicians, patients, and their families viewed lobotomy and analyzes the reasons for its overwhelming use.